Factors affecting the activity patterns of Myotis tricolor (Chiroptera: Vespertilionidae) - Jordaan, Stacey (Department of Biological Sciences, 2015)
Foraging behaviour is an important component of an animal’s ecology. Increases in energetic costs associated with reproduction, should have marked effects on foraging behaviour, but may be compounded by the effects of environmental factors. I investigated the activity patterns of female M. tricolor over the reproductive period using radio telemetry. Six female bats were radio-tagged during each reproductive period: early pregnancy, late pregnancy and lactation. Times at which bats entered and exited the cave were recorded, as was the temperature, moon-phase, cloud cover, wind speed, rainfall and insect abundance. These data were used to calculate emergence time, number of foraging bouts and foraging duration for each reproductive period, which were then correlated with the environmental variables.